2016
DOI: 10.1021/acs.jafc.6b00091
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Antibiotic Residues in Aquatic Products in Urban and Rural Areas of Vietnam

Abstract: Antibiotic residues in aquatic products in Vietnam were investigated. A total of 511 fish and shrimp samples were collected from markets in Ho Chi Minh City (HCMC), Thai Binh (TB), and Nha Trang (NT) from July 2013 to October 2015. The samples were extracted with 2% formic acid in acetonitrile and washed with dispersive C18 sorbent. Thirty-two antibiotics were analyzed by LC-MS/MS. Of the 362 samples from HCMC, antibiotic residues were found in 53 samples. Enrofloxacin was commonly detected, at a rate of 10.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 22 publications
3
17
0
1
Order By: Relevance
“…(100%). This result is in line with a previous survey of shrimps from local markets in the Red River and Mekong Delta regions of Vietnam (13.0% and 33.3%, respectively) (Pham et al, 2015), but higher than previous results reported from the Vietnamese provinces of HCMC, Thai Binh and Nha Trang (8.8, 1.8 and 3.2%, respectively) (Uchida et al, 2016). However, we were only able to establish the identity of the antimicrobial residue in 4 of 9 samples that tested positive by a bacterial inhibition test.…”
Section: Discussionsupporting
confidence: 92%
“…(100%). This result is in line with a previous survey of shrimps from local markets in the Red River and Mekong Delta regions of Vietnam (13.0% and 33.3%, respectively) (Pham et al, 2015), but higher than previous results reported from the Vietnamese provinces of HCMC, Thai Binh and Nha Trang (8.8, 1.8 and 3.2%, respectively) (Uchida et al, 2016). However, we were only able to establish the identity of the antimicrobial residue in 4 of 9 samples that tested positive by a bacterial inhibition test.…”
Section: Discussionsupporting
confidence: 92%
“…Enrofloxacin was most prevalent antimicrobial, which was detected in 13.4 and 7.5% of fish and shrimp in Ho Chi Minh city, respectively. Fish was not contaminated with oxolinic acid, while shrimp was not contaminated with e Modified by the data described in Uchida et al (2016). Chicken, pork, and beef include meat and internal organs such as heart, river, etc.…”
Section: Residual Antimicrobial In Various Foods and Environmental Wamentioning
confidence: 99%
“…Yang et al 9 reported residues of quinolones in fish in Guangzhou. Antibiotics were detected in aquatic products of Ningbo, Beijing, Shanghai 10 , India 11 , Vietnam 12 , South Carolina, and Georgia 13 . China is not only a major producer of antibiotics but also a major user 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%